Cloud Computing in Education: A Revolution in Learning Management Systems - Sikarwar, Prerana; Tiwari, Archana; Joshi, Ritesh; Agrawal, Jyoti (Innovare Journal of Education, 2025)
The transformation in the educational environment with cloud-based learning Management Systems (LMSs) has significantly affected the education world. This systematic review aimed to examine the impact of cloud-based LMSs on pedagogy and learning, including the present status, advantages, challenges, and future possibilities of digital education. In addition, the bibliographic analysis was carried out using Dimension.ai. Cloud-based LMSs such as Moodle, 360Learning, Canvas, and Google Classroom have transformed educational delivery by offering scalable and adaptive solutions that exceed the limitations of conventional education systems. Here, several previous studies have shown that cloud technologies have significantly transformed education by improving access to educational materials, fostering collaboration, and enabling personalized learning. Moreover, the results of the bibliographic analysis showed that the collection of almost 604580 documents highlights a broad spectrum of scholarly interests. The collection shows a dynamic research environment using open scientific approaches. On the other hand, implementing cloud-based LMSs presents significant challenges, including the need for extensive training for both educators and learners, as well as compatibility with diverse technical infrastructures across various educational settings. The primary themes are cost-effectiveness, scalability, accessibility, and data management, while the foremost problems are security, data privacy, and user adaptation. The findings of this study have revealed the significance of cloud computing in enabling educational institutions to provide students with inclusive, scalable, and adaptive learning environments.